GenNet: A Platform for Hybrid Network Experiments - Kispersky, Tilman J.; Economo, Michael N.; Randeria, Pratik; White, John A. (Frontiers in Neuroinformatics, 2011)
We describe GenNet, a software plugin for the Real Time Experimental Interface (RTXI) dynamic clamp system that allows for straightforward and flexible implementation of hybrid network experiments. This extension to RTXI allows for hybrid networks that contain an arbitrary number of simulated and real neurons, significantly improving upon previous solutions that were limited, particularly by the number of cells supported. The benefits of this system include the ability to rapidly and easily set up and perform scalable experiments with hybrid networks and the ability to scan through ranges of parameters. We present instructions for installing, running and using GenNet for hybrid network experiments and provide several example uses of the system.